Accessibility and active offer: Health care and social services in linguistic minority communities - Drolet, Marie; Bouchard, Pier; Savard, Jacinthe (University of Ottawa Press, 2017)
This edited volume examines language issues within the active offer of health and social services in francophone and anglophone minority communities. Action based, it will help shape the leaders of tomorrow. It is imperative that we train leaders who are able to intervene efficiently with service users and to support a better organization of the workplace. It is especially important to look at the many issues related to postsecondary training and human resources, such as recruiting and keeping these leading professionals. Accessibility and Active Offer thus combines theory and empirical data to help future professionals understand the workplace issues of accessibility and active offer of minority-language services. This English-language adaptation of Accessibilité et offre active features an additional chapter by Richard Bourhis on issues specific to Anglophone communities in Québec.

Accessibilité et offre active : Santé et services sociaux en contexte linguistique minoritaire - Drolet, Marie; Bouchard, Pier; Savard, Jacinthe (Presses de l'Université d'Ottawa, 2017)
Ce collectif multidisciplinaire examine les enjeux linguistiques de l’offre active des services sociaux et de santé en français aux communautés francophones en situation minoritaire. Dirigé vers l’action, il contribue à la formation de leaders capables d’intervenir efficacement. Pour les communautés francophones en situation minoritaire (CFSM), l’offre active des services de santé et des services sociaux en français est une question de qualité, de sécurité, d’humanisation des soins et services, de droit et d’équité, et d’éthique professionnelle. Les enjeux liés à la formation postsecondaire et aux ressources humaines, notamment au recrutement et à la rétention des professionnels, sont particulièrement importants, car il est essentiel de former les leaders de demain. Ainsi, cet ouvrage combine la théorie et les données empiriques pour se diriger vers l’action afin de permettre aux futurs professionnels de mieux saisir les enjeux de l’accessibilité et de l’offre active de services en français qui se posent en milieu de travail.

Introduction : Vers une compréhension des acteurs, du système et des leviers d’action - Drolet, Marie; Bouchard, Pier; Savard, Jacinthe; van Kemenade, Solange (Accessibilité et offre active : Santé et services sociaux en contexte linguistique minoritaire, 2017)
Cette introduction présente le fil conducteur du livre, ainsi qu'une introduction à chacun de ses chapitres